Could the Prevalence and Distribution of Os Supratrochleare Dorsale and Patella Cubiti be the Key to Accurate Diagnosis? - Aksu, F.; Akkoc, R. F.; Aydin, S. (Springer Heidelberg, 2022)
Background The aim of this study was the prevalence of patella cubiti and os supratrochleare dorsale, and to detect the differences between genders. Materials and Methods In the study, direct radiographs of 1646 people (959 females and 687 males), who presented to Firat University Hospital between 01.01.2016 and 31.01.2019 and had elbow joint radiographs, were evaluated retrospectively. Of the radiographs evaluated, 346 were right and left elbow radiographs of the same people, 689 were just right elbow radiographs, and 611 were only left elbow radiographs. Results The prevalence of os supratrochleare dorsale was 2.08% (20 in 959 women) in women, 2.62% (18 in 687 men) in men, and 2.3% (38 in 1646 people) in total. The prevalence of patella cubiti was found to be 0.42% (4 in 959 women) in women, 1.31% (9 in 687 men) in men, and 0.79% (13 in 1646 people) in total. In addition, the prevalence of both sesamoid bones only in the left elbow and in both elbows was determined with and without separation according to male-female genders. Conclusion We are of the opinion that knowing the prevalence and distribution of these sesamoid bones will help with establishing early and correct diagnoses for patients who present with complaints, such as elbow extension limitation and pain in the elbow area.
Keywords: Elbow joint; Direct radiography; Sesamoid bone; Patella cubiti; Os supratrochleare dorsale